2015
DOI: 10.2135/cropsci2014.10.0738
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reference Genes for RT‐qPCR Normalization in Cowpea under Drought Stress during Biological Nitrogen Fixation

Abstract: Reverse transcription–quantitative polymerase chain reaction (RT‐qPCR) has emerged as an important technique for gene‐expression analysis. However, for accurate and reliable results, the data normalization using appropriated reference genes is critical, and a systematic validation of reference genes in cowpea (Vigna unguiculata L. Walp), a high stress‐tolerant leguminous, has not been performed. To provide suitable reference genes in this strategic leguminous species under drought stress, we evaluated the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Therefore, in order to ensure the reliability and precision of qPCR data, the MIQE guidelines [ 5 ] was applied for the acquisition of the results presented here (Additional file 4 : Table S1). There is a lack of a systematic validation of RGs in cowpea (i.e., out of five works [ 13 17 ] addressing this theme, four omitted any information on how RGs expression stability and primer efficiency were evaluated). The present work represents a pioneering effort for a detailed analysis of candidate RGs in tolerant and sensitive cowpea cultivars in response to abiotic stresses (root dehydration and salt) rigorously tested for effective normalization of the qPCR data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to ensure the reliability and precision of qPCR data, the MIQE guidelines [ 5 ] was applied for the acquisition of the results presented here (Additional file 4 : Table S1). There is a lack of a systematic validation of RGs in cowpea (i.e., out of five works [ 13 17 ] addressing this theme, four omitted any information on how RGs expression stability and primer efficiency were evaluated). The present work represents a pioneering effort for a detailed analysis of candidate RGs in tolerant and sensitive cowpea cultivars in response to abiotic stresses (root dehydration and salt) rigorously tested for effective normalization of the qPCR data.…”
Section: Discussionmentioning
confidence: 99%
“…However, few works have focused on the selection of RGs in cowpea based on different statistical software. The first study was conducted by Da Silva et al [ 17 ], who evaluated the expression stability of eight candidate genes in cowpea under drought stress during biological nitrogen fixation, using geNorm and NormFinder algorithms. The genes of the regulatory subunit of phosphatase 2A protein ( VuPp2A ) and polyubiquitin 28 ( VuUbq28 ) were the best normalizers suggested by both algorithms, for global analysis (nodules and leaves tissues).…”
Section: Introductionmentioning
confidence: 99%
“…4B.2), were selected for further expression analysis studies. Both genes have been described as being involved in abiotic stress responses and were previously reported to be up-regulated in cowpea leaves under drought stress (Da Silva et al, 2015;Iuchi et al, 1996;Simoes-Araujo et al, 2008). VuCPRD14 gene was characterized by Iuchi et al (1996) being involved in the synthesis of different compounds, such as anthocyanin and medicarpin, which protect plant cells from stress conditions, having a role on dehydration response (Guo et al, 1994;Iuchi et al, 1996).…”
Section: Could Gene-expression Profiling Be Used To Screen Cowpea Dromentioning
confidence: 99%
“…upregulated in drought-tolerant cultivars from different crops under water deficit conditions (Sato and Yokoya, 2008;Temel et al, 2017). For comparison, VuEF1-α and VuPp2A genes were selected as reference genes due to their stability under drought stress conditions (Da Silva et al, 2015;Weiss et al, 2018). Gene expression analysis by qPCR revealed that both DG genes were mostly expressed at 25% and 0% of FC treatments (Fig.…”
Section: Could Gene-expression Profiling Be Used To Screen Cowpea Dromentioning
confidence: 99%
“…To identify differentially expressed genes, many technologies such as microarray, DNA chip-based array, genome-wide transcript profiling, and quantitative real-time PCR (qRT-PCR) have been deployed in a number of studies (Ozturk et al, 2002 ; Degenkolbe et al, 2009 ; Lenka et al, 2011 ). qRT-PCR is the most commonly used approach for expression analysis of genes in many crop species including pigeonpea (Borges et al, 2012 ; Qiao et al, 2012 ; Deeplanaik et al, 2013 ; Recchia et al, 2013 ; Turyagyenda et al, 2013 ; Da Silva et al, 2015 ; Sinha et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%